1993
DOI: 10.1016/0014-5793(93)81423-w
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐oxidants and mitochondrial Ca2+: their relationship to apoptosis and oncogenesis

Abstract: Apoptosis is a physiological process for active cell removal. One of its hallmarks is an increased cytosolic Ca2+ content. Several genes involved in apoptosis control have been identified, but their mode of action is not understood in detail. Apoptosis may relate to oncogenesis, in that some malignant tumors may grow because genes engaged in apoptosis control are altered. L929 cells overexpressing the proto‐oncogen bcl‐2 have an increased mitochondrial membrane potential (δψ), as have many carcinoma cells, bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
123
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(128 citation statements)
references
References 53 publications
4
123
0
Order By: Relevance
“…3), which might be largely associated with production of ROS in the apoptotic process. ROS generation has been implicated in the apoptotic process and could elicit the expression of HO-1 [20,21]. Previous research showed that SVCV infection could induce apoptosis in EPC cells [22], which could result in the increase of HO-1 expression from 12 h to 24 h postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…3), which might be largely associated with production of ROS in the apoptotic process. ROS generation has been implicated in the apoptotic process and could elicit the expression of HO-1 [20,21]. Previous research showed that SVCV infection could induce apoptosis in EPC cells [22], which could result in the increase of HO-1 expression from 12 h to 24 h postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BHA did not interact directly with BVDV, since preincubation of the virus with BHA for 1 h at 37 mC did not reduce virus infectivity (not shown). Additionally, BHT (Gogvadze et al, 1992) and cyclosporine A (CSA) (Schweizer et al, 1993) inhibit ROS-induced Ca# + -cycling in mitochondria, an important factor in ROS-induced apoptosis (Richter, 1993). However, BHT was much more toxic to BT cells than was BHA, which is also observed in hepatocytes (Thompson & Molde!…”
Section: Discussionmentioning
confidence: 99%
“…This delayed recovery could increase cytosolic, mitochondrial, and nuclear calcium, alter cellular excitability and signaling, and ultimately lead to apoptosis (Nicotera and Orrenius, 1992;Brini et al, 1993Brini et al, , 1994Richter, 1993;Dykens, 1994;Ghosh and Greenberg, 1995;Oshimi and Miyazaki, 1995;Khan et al, 1996;Simpson and Russell, 1996;Tong et al, 1996).…”
Section: Discussionmentioning
confidence: 99%